2007
DOI: 10.1086/512605
|View full text |Cite
|
Sign up to set email alerts
|

The Remarkable Afterglow of GRB 061007: Implications for Optical Flashes and GRB Fireballs

Abstract: We present a multiwavelength analysis of Swift GRB 061007. The 2 m robotic Faulkes Telescope South began observing 137 s after the onset of the -ray emission, when the optical counterpart was already decaying from R $ 10:3 mag, and continued observing for the next 5.5 hr. These observations begin during the final -ray flare and continue through and beyond a long, soft tail of -ray emission whose flux shows an underlying simple power-law decay identical to that seen at optical and X-ray wavelengths, with tempor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 50 publications
8
96
0
1
Order By: Relevance
“…[See the electronic edition of the Journal for a color version of this figure. ] to event and that all events should exhibit an X-ray plateau. However, there are few bursts-<10% of the 30 or so afterglow observations that began early and measured with high signal-tonoise ratio the tail of the prompt emission-that do not show early HR variation and do appear to show an afterglow-like component decaying as a power law after the prompt emission at t k100 s. The best example GRBs, namely, GRB 050717 (see also Krimm et al 2006), GRB 060105 (see also Tashiro et al 2007), and GRB 061007 (see also Mundell et al 2007;Schady et al 2007), are shown in Figure 7. These have especially bright and hard prompt emission with E peak k 500 keV (suggestive of high À) and hard X-ray emission detected beginning after t % 90 s with energy index % 1.…”
Section: Events With No Hardness Variationmentioning
confidence: 98%
“…[See the electronic edition of the Journal for a color version of this figure. ] to event and that all events should exhibit an X-ray plateau. However, there are few bursts-<10% of the 30 or so afterglow observations that began early and measured with high signal-tonoise ratio the tail of the prompt emission-that do not show early HR variation and do appear to show an afterglow-like component decaying as a power law after the prompt emission at t k100 s. The best example GRBs, namely, GRB 050717 (see also Krimm et al 2006), GRB 060105 (see also Tashiro et al 2007), and GRB 061007 (see also Mundell et al 2007;Schady et al 2007), are shown in Figure 7. These have especially bright and hard prompt emission with E peak k 500 keV (suggestive of high À) and hard X-ray emission detected beginning after t % 90 s with energy index % 1.…”
Section: Events With No Hardness Variationmentioning
confidence: 98%
“…On the other hand, the color evolution of the afterglow of GRB 061126 (Perley et al 2008c) goes from redder to bluer, similar to the case of the very well sampled early afterglow of GRB 080319B Racusin et al 2008;Woźniak et al 2009). Several other afterglows show no early color changes at all, e.g., those of GRB 060418 and GRB 060607A (Molinari et al 2007;Nysewander et al 2009b) and GRB 061007 (Mundell et al 2007b;Schady et al 2007b).…”
Section: The Luminosity Distribution At Early Times: Diversity and CLmentioning
confidence: 99%
“…Finally, the derived very high extinction for GRB 060210 is unsure (see Appendix B.3 for more details), implying that the afterglow, which seems to show a standard (not rapid, like GRB 050904 and GRB 080319B) decay after a short plateau and peak, may be much less luminous. Excluding these special events, the early afterglow of GRB 061007 (Mundell et al 2007b;Schady et al 2007b) is the most luminous in the sample, although it decays rapidly. 68 Between 0.01 and 0.5 days, the afterglow of GRB 090313 is the most luminous, though we caution that so far, we have only an extensive GCN data set.…”
Section: Does An Upper Limit On the Forward Shock Luminosity Exist?mentioning
confidence: 99%
See 1 more Smart Citation
“…We finally note that there are several sources that exhibit optical light curves analogous to GRB 061121, that is, GRB 021004 (Uemura et al 2002), GRB 050525A (Klotz et al 2005;Blustin et al 2006), GRB 060117 (Jelínek et al 2006), GRB 060526 (Dai et al 2007), and GRB 061007 (Mundell et al 2007). For all of them, an early decay phase was terminated by a flattening or a hump at 10 2−4 s, which was followed by a steeper decay phase.…”
Section: Implication To the Synchrotron-shock Modelmentioning
confidence: 83%